2022
DOI: 10.1093/infdis/jiac116
|View full text |Cite
|
Sign up to set email alerts
|

A Cohort Study on the Duration of Plasmodium falciparum Infections During the Dry Season in The Gambia

Abstract: Background In areas where Plasmodium falciparum malaria is seasonal, a dry season reservoir of blood-stage infection is essential for initiating transmission during the following wet season. Methods In The Gambia, a cohort of 42 individuals with qPCR positive P. falciparum infections at the end of the transmission season (December) were followed monthly until the end of the dry season (May) to evaluate infection persistence. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…Similar to a few previous studies, we found that asymptomatic infections had a higher COI than symptomatic infections across both the coastal mainland and Zanzibar parasite populations (Sarah-Matio et al, 2022). Potential reasons for this phenomenon include low level immune response resulting in chronic infection with multiple clones over time in asymptomatic individuals (Felger et al, 2012), and dominance of more virulent clones in shorter symptomatic infections resulting in lower COI (Collins et al, 2022). In Zambia, one study suggested that infections that cause asymptomatic infection may be genetically different than those that cause symptomatic infection (Searle et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to a few previous studies, we found that asymptomatic infections had a higher COI than symptomatic infections across both the coastal mainland and Zanzibar parasite populations (Sarah-Matio et al, 2022). Potential reasons for this phenomenon include low level immune response resulting in chronic infection with multiple clones over time in asymptomatic individuals (Felger et al, 2012), and dominance of more virulent clones in shorter symptomatic infections resulting in lower COI (Collins et al, 2022). In Zambia, one study suggested that infections that cause asymptomatic infection may be genetically different than those that cause symptomatic infection (Searle et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The exact duration of these infections was impossible to estimate with precision, given the 4-week interval between scheduled visits, but it is evident that the majority of infections were brief and spontaneously cleared. While naturally acquired immunity has been suggested as determinant of infection clearance 32 , recent analyses suggest that infection duration may be shortest in young children 30 and acquired immunity may actually be a prerequisite to sustain chronic infections 33 , rendering a role of immunity-dependent infection clearance less obvious. Importantly, we provide the first evidence that these short-duration infections do not result in measurable gametocyte densities.…”
Section: Discussionmentioning
confidence: 99%
“…33 gametocytes per µl (IQR 2.56-97.68) among incident asymptomatic infections. Analyzing dynamics of gametocyte densities over the course of infections, 28.1% (9/32) of peak gametocyte densities occurred at the initial visit, 50%(16/32) occurred after the initial visit but by week 4, and 21.9% (7/32) occurred at a timepoint beyond week 4.…”
mentioning
confidence: 99%
“…The exact duration of these infections was impossible to estimate with precision, given the 4-week interval between scheduled visits, but it is evident that the majority of infections were brief and spontaneously cleared. While naturally acquired immunity has been suggested as determinant of infection clearance (Bruce et al, 2000; Felger et al, 2012; Nguyen et al, 2018), recent analyses suggest that infection duration may be shortest in young children (Briggs et al, 2020) and acquired immunity may actually be a prerequisite to sustain chronic infections (Collins et al, 2022), rendering a role of immunity-dependent infection clearance less obvious. Importantly, we provide the first evidence that these short-duration infections do not result in measurable gametocyte densities.…”
Section: Discussionmentioning
confidence: 99%